In memoriam - Oscar Altimir (CEPAL Review, 2018)
As we prepare this edition of CEPAL Review, our editorial team wishes to express its deep sorrow upon the death of Oscar Altimir on 27 September in Santiago. His departure is deeply felt by the ECLAC community, especially by those of us involved in the production of CEPAL Review. We acknowledge the intellectual legacy of Altimir, who directed this publication between 1996 and 2008, succeeding its first two directors: Aníbal Pinto Santa Cruz (1986–1996) and founder Raúl Prebisch (1976–1986). This editorial is intended to convey our heartfelt homage to Altimir’s academic figure and distinguished career as a leading development economist in the region and as one of the most prominent thinkers of the Economic Commission for Latin America and the Caribbean (ECLAC) over the past 40 years.